Association of Claustrophobia and Anxiety with Cast Intolerance in Patients with Extremity Injuries. Issue 2 (December 2020) - Urch, Ekaterina; Kim, Julia M.; Rancy, Schneider K.; Saltzman, Eliana B.; Lee, Steve K.; Wolfe, Scott W.
Background: Patients undergoing casting for upper or lower extremity injuries may present with recalcitrant pain without an identifiable physiologic etiology, which increases the likelihood of more frequent or unscheduled office visits, insomnia, decreased patient satisfaction, unnecessary investigative procedures or treatments, and—in some cases—cast intolerance. The exact causes of cast intolerance are not well studied, although claustrophobia and associated fears of suffocation and restriction may be underlying causes. Questions/Purposes: We sought to explore the association between claustrophobic tendencies and cast intolerance. We hypothesized that patients with claustrophobia or claustrophobic tendencies would have a higher rate of cast intolerance. Methods: Patients requiring circumferential casting of an upper or lower extremity were prospectively enrolled at the time of cast application. Data were collected at each office visit until cast removal. Pre- and post-casting anxiety were quantified using the Beck Anxiety Inventory ® (BAI ® ). Pain was assessed at each visit using the visual analog scale (VAS). Claustrophobic tendencies were evaluated after cast removal using the Claustrophobia Questionnaire (CLQ). At the completion of the study, patients were assigned to either the cast-tolerant or the cast-intolerance cohort according to predetermined criteria. CLQ, BAI, and VAS scores were compared between cohorts. Results: Out of 199 patients enrolled, 4% ( n = 8) met the criteria for cast intolerance. There was no difference in BAI (anxiety) scores between groups at casting, but cast-intolerant patients had significantly lower post-casting BAI scores than the cast-tolerant controls, indicating a decrease in anxiety after cast removal. Taken together, both groups demonstrated significant reduction in VAS scores from casting to cast removal. The tolerant group had a significant reduction in VAS scores, whereas the intolerant group did not. The intolerant group had a significant negative correlation between initial VAS scores and final BAI scores. The tolerant group had a significant positive correlation between initial VAS scores and final BAI scores, as well as between final VAS scores and final BAI scores. Interestingly, no difference in CLQ scores was seen between groups, although there were positive correlations between CLQ scores and pre- and post-casting anxiety scores and between CLQ and final VAS scores. Conclusions: Our hypothesis was not supported. Although we did not find a relationship between claustrophobia and cast intolerance, we did find significant correlations between anxiety and pain. The tolerant group's initial and final pain scores had significantly positive correlations to final anxiety, suggesting that pain is likely to cause or increase anxiety; indeed, as pain decreased, so did anxiety. The intolerant group, however, had a significant negative correlation between initial pain and final anxiety scores. It would not be expected that lower pain scores would increase anxiety. This may suggest that cast-intolerant patients experience or report their anxiety as pain. These findings may explain why some patients suffer from pain that cannot be explained by an underlying physiologic process and is resistant to traditional pain management. A multidisciplinary approach, including psychological and psychosocial assessments, may help identify nonphysiologic components to pain. An accurate diagnosis for the cause of pain may lead to nonpharmacological interventions and therefore reduce opioid use and overall costs and improve patient outcomes.